Developing transformative community-university partnerships: a participatory assessment of Rhodes University community engagement monitoring and evaluation system - Nkwinti, Nosipho (Rhodes University, Faculty of Education, Department of Secondary and Post-School Education)
This thesis comprehensively explores transformative community engagement (CE) in higher education, focusing on the context of collaborative community-university partnerships (CUPs) in Makhanda, South Africa. The study aimed to assess and revise the monitoring and evaluation (M&E) system of the Rhodes University Community Engagement division to foster a transformation in CUPs. The research employs an exploratory design to understand the complexities of CUPs and improve the M&E systems by generating new concepts and ideas. A variety of qualitative methods, including focus groups, interviews, and document analysis, were utilized to engage community partners, student leaders, and Rhodes University Community Engagement staff. The participatory approach to research was critical, involving stakeholders in finalizing the M&E framework to ensure it met the shared objective. Data analysis was conducted inductively, with themes emerging from the data to facilitate a bottom-up understanding of the research questions. The study found that diverse community engagement projects at Rhodes University enhanced partnerships between the university and the local community in Makhanda. Participants shared varied understandings and experiences of Community Engagement. They saw CE as crucial for bridging the university-community divide and aiding local development. Furthermore, the research identified the need for a Monitoring and Evaluation system that supports collaborative Community-University Partnerships. Participants collaboratively developed and refined this M&E system, ensuring it aligns with community needs and promotes sustained development in Makhanda. Challenges such as diverse perspectives, logistical issues in focus groups, and power dynamics were also highlighted and addressed through an inclusive and participatory approach. This research highlights the elaborate distinctions of community engagement and the importance of such partnerships in fostering sustainable societal development. The framework developed has practical implications for shaping policies, fostering inclusivity, and promoting responsive university-community engagement that is aligned with community needs. The research concludes by suggesting the value of inclusivity, communication, and a flexible adaptation of practices to maximize the benefits of such partnerships. Future research could explore the longitudinal impacts of university-community partnerships, examine the scalability of the current framework to other universities, and evaluate the long-term socio-economic outcomes of the engaged citizen program on the community.
Keywords: Community engagement; Community and college -- South Africa -- Eastern Cape; Rhodes University; Collaboration; Social change